2004
DOI: 10.1002/chin.200424205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent on the Microstructures of Nanostructured Bi2Te3 Prepared by Solvothermal Synthesis.

Abstract: Synthesis. -Nanoparticles of the title compound with average sizes of 15-20 nm and nanowires with a diameter less than 100 nm and a length of about 10 µm are synthesized solvothermally at 150°C from BiCl3 and Te powder using NaBH4 as reductant in various solvents such as en, DMF, Py, acetone, EtOH, and H2O. The samples are characterized by XRD and TEM. The phase distributions, microstructures, and grain sizes of the nanostructured Bi 2 Te 3 products are related to the dielectric constant and surface tension of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…By comparing with the physical and chemical properties of the solvents used, it is found that deionized water has the biggest dielectric constant (dielectric constant=78.304, 36.71, 25.7, 20.7, 12.9 for deionized water, DMF, ethanol, acetone, and en, respectively) and that their other properties are similar [24]. Therefore, the dielectric constant of a solvent probably has a significant effect on the formation of the Bi 2 Se 3 compound.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing with the physical and chemical properties of the solvents used, it is found that deionized water has the biggest dielectric constant (dielectric constant=78.304, 36.71, 25.7, 20.7, 12.9 for deionized water, DMF, ethanol, acetone, and en, respectively) and that their other properties are similar [24]. Therefore, the dielectric constant of a solvent probably has a significant effect on the formation of the Bi 2 Se 3 compound.…”
Section: Resultsmentioning
confidence: 99%
“…Тому висновки щодо росту Z на основі підвищен-ня потрібно робити виважено. Для підвищення ZT зусилля вчених великою мірою зосередилися на підході з використанням нанооб'ємних структур, таких як наночастинки [22][23][24][25], нанотрубки [26][27][28], і нанодроти [29][30][31]. У цих наноструктурах проявляється ефект фоно-нного розсіяння, який знижує теплопровідність.…”
Section: еволюція уявлень про ефективність термоелектроперетворювачівunclassified
“…Bismuth telluride and its alloys are currently best-known materials for TE cooling devices due to their highest TE performance for operation at room temperature [20]. The attempts to fabricate low-dimensional bismuth telluride have been made in various ways such as chemical alloying method by coprecipitation [21], reverse micelle method [22], hydrothermal [23,24] and solvothermal method [25,26], elimination reaction method [27], organometallic method [28], electrochemical deposition [29,30] etc. Shape and size tailoring becomes very critical since the overall TE figure of merit can be determined by the nanostructure of low-dimensional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Shape and size tailoring becomes very critical since the overall TE figure of merit can be determined by the nanostructure of low-dimensional materials. The previous cases [21][22][23][24][25][26][27][28][29][30] have indicated that the shape and size control is not easy to achieve. In this study, bismuth telluride nanocrystals are fabricated via solvothermal method and their size and shape are tailored by surfactants during solvothermal reactions and ultrasonication in the post-process.…”
Section: Introductionmentioning
confidence: 99%